Spatial and temporal controls on pinyon and juniper seedling establishment in the Uncompahgre Plateau, western Colorado - Graeve, Phillip Jay, author; Rocca, Monique, advisor; Brown, Peter, committee member; Sibold, Jason, committee member (Colorado State University. Libraries, 2012)
Moderate and extreme climate events have the potential to cause sudden shifts with long-lasting relictual effects in ecological communities. In this study I investigated the direct and indirect effects of climate on Colorado pinyon (Pinus edulis) and Utah juniper (Juniperus osteosperma) on the Uncompahgre Plateau in western Colorado. I determined age structure of pinyon seedlings and tested for the effects of current year and antecedent year climate on seedling establishment. Finally, I described microhabitat preferences (substrate microhabitat and overstory canopy) for pinyon and juniper seedlings and assessed whether suitable microhabitats may have changed as a consequence of overstory die-off. No relationships between climate and pinyon establishment were detected, and pinyon establishment appears to have been relatively constant over the past 30 years. I found that both pinyon and juniper exhibited distinct preferences for certain substrate microhabitats, especially different types of litter. Pinyon seedlings avoided bare soil microhabitats. While both pinyon and juniper seedlings avoided open overstory microhabitat, pinyon preferred juniper overstory microhabitat. Microhabitat preferences of pinyon seedlings may buffer seedlings from climate-induced stress. Pinyon overstory declined rapidly due to a severe drought from 2000-2004, but juniper overstory was not affected. My results indicate that episodic overstory mortality events and continuous pinyon establishment characterize pinyon dynamics on the Uncompahgre Plateau, at least within the 30 year time frame investigated here. In contrast, juniper seedlings are less abundant but likely more resilient to climate-induced changes in microhabitat structure. Future pinyon establishment and overstory survival may be reduced due to direct and indirect effects of climate, especially if predictions for increased drought frequency and severity for this area are realized.
Keywords: climate; dendrochronology; establishment; juniper; pinyon; seedling